EPISTEMOLOGI DAN AKSIOLOGI PENGOPERASIAN RAPORT DIGITAL MADRASAH DI MTsN 1 MERANGIN - Hidayatul Fadliah; Rhamdani Rhamdani; Eka Kurniawati; Renny Yuliarti; Riska Meisyi Putri; Anggia Pratiwi; Elfa Eriyani (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the digital transformation of education through the implementation of the Madrasah Digital Report System (Raport Digital Madrasah/RDM) at MTsN 1 Merangin by examining epistemological, axiological, and ontological dimensions as foundations for understanding changes in teachers’ professional practices in the digital era. Method: This study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing to gain an in-depth understanding of the phenomenon under investigation. Results: The findings indicate that the successful implementation of RDM is supported by firm managerial regulations and collaborative initiatives among teachers to strengthen information technology competencies. However, implementation remains challenged by intergenerational gaps in digital literacy and limitations in network infrastructure that affect system effectiveness. The philosophical analysis further reveals that the use of digital technology in academic reporting requires rational cognitive validation and adherence to ethical principles to ensure the protection of students’ academic privacy in digital environments.